Pengaruh Beban Kerja dan Stres Kerja Terhadap Kepuasan Kerja Karyawan dengan Work-Life Balance sebagai Variabel Mediasi pada Karyawan di Industri Pertambangan - Kusumawati, Winda; Linando, Jaya Addin (Universitas Hamzanwadi, 2024)
This research aims to examine the correlation of job stress and workload on employee job satisfaction in the mining sector, where work-life balance is the become mediation. With a population of all employees working in the mining sector, so that the sample of this research was 150 respondents conducted using the Lemeshow formula as a method of determining the sample size. The data collection method was carried out by distributing questionnaires to mining employees. And with data analysis using SPSS 21.0 for Windows software. This research uses descriptive analysis, sobel test, and t test. The result of the study state that workload has a negative effect on work-life balance, job stress has a negative effect on work-life balance, workload has a negative effect on job satisfaction, job stress has a negative effect on job satisfaction. While work-life balance has a positive effect on job satisfaction. And work-life balance can mediate the influence of workload and job stress on job satisfaction.